The Character of Responsibility and Honesty: Its Impact on Science Learning Outcomes - Syofyan, Harlinda; Rosyid, Ainur; Febrianti, Nurul; Ratih, Ratih (Universitas Pendidikan Ganesha, 2022)
The negative impact felt during the pandemic experienced by lecturers in online learning as it is today is the difficulty in giving a humanist touch to students, one of which is ethics education with the name character education. Character education is an essential thing to be instilled in students and students. When online learning is like today, it is responsibility and honesty that are important to keep in check. But in fact, the character of commitment and honesty is ignored by students. This study aims to analyze the relationship between the character of responsibility and honesty on learning outcomes in Natural Sciences. This research is quantitative research using the survey method. The subjects involved in this study were 170 students. Data collection is done by distributing questionnaires to respondents. The collected data was then analyzed by several tests, namely data description analysis test, regression test, normality test, correlation test, determination test, t-test, and F test. The results showed that F-count = 9.780 > F-table = 3.05 with a significant 0.000 <0.05, which means that there is a positive and significant influence between responsibility and honesty simultaneously on science learning outcomes. Based on these findings, teachers should pay attention to the character of responsibility and honesty and continue to develop these characters in students.